Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Here is the integral
$$\int_0^\infty \lfloor x \rfloor e^{-x}dx$$

Here is what I have so far:
$$I = \sum_{n=0}^\infty \int_n^{n+1} n e^{-x}dx$$ $$ = \sum_{n=0}^\infty -ne^{-n-1} + ne^{-n}$$ $$ = \sum_{n=0}^\infty -ne^{-n-1} + ne^{-n}$$ $$ = \sum_{n=0}^\infty ne^{-n}(1 -e^{-1})$$ $$ = (1 -e^{-1})\sum_{n=0}^\infty ne^{-n}$$ $$ = (1 -e^{-1})\sum_{n=0}^\infty \sum_{k=0}^{\infty} \frac{-(-n)(-n)^k}{k!}$$ $$ = (1 -e^{-1})\sum_{n=0}^\infty \sum_{k=0}^{\infty} \frac{-(-n)^{k+1}}{k!}$$ $$ = (1 -e^{-1})\sum_{n=0}^\infty \sum_{k=0}^{\infty} \frac{-(-n)^{k+1}}{(k+1)!}(k+1)$$ $$ = (1 -e^{-1})\sum_{n=0}^\infty \sum_{k=0}^{\infty} \frac{-k(-n)^{k+1}}{(k+1)!} + \frac{-(-n)^{k+1}}{(k+1)!}$$

$$ = (1 -e^{-1})\sum_{n=0}^\infty (1-e^{-n})[\sum_{k=0}^{\infty} \frac{-k(-n)^{k+1}}{(k+1)!}]$$

At this point I gave up.

share|cite|improve this question
If you let $I=\sum_{n=0}^{\infty}n e^{-n}$ and take a look at $I/e$, I think you can find a way to compute it easily. – Patrick Li Feb 16 '13 at 1:48
Mark, you can get a genuine summation symbol with \sum; \Sigma doesn’t size properly. – Brian M. Scott Feb 16 '13 at 1:53
up vote 8 down vote accepted

You have

$$\begin{align*} \sum_{n\ge 0}\int_n^{n+1}ne^{-x}dx&=\sum_{n\ge 0}n\left[\frac1{e^x}\right]_{n+1}^n\\\\ &=\sum_{n\ge 0}n\left(\frac1{e^n}-\frac1{e^{n+1}}\right)\\\\ &=\left(1-\frac1e\right)\sum_{n\ge 0}\frac{n}{e^n}\;.\tag{1} \end{align*}$$

Now $$\frac1{1-x}=\sum_{n\ge 0}x^n$$ for $|x|<1$, so, differentiating and multiplying by $x$, we have

$$\frac{x}{(1-x)^2}=\sum_{n\ge 0}nx^n\;.\tag{2}$$

Substitute $x=e^{-1}$, and $(1)$ becomes


$(2)$ is a useful formula; it’s worth at least remembering how to derive it.

share|cite|improve this answer
Beautiful! I would have not thought to use the derivative. – Mark Feb 16 '13 at 2:06

Note that,

$$ \sum_{k=0}^{\infty} e^{-k x} = \frac{1}{1-e^{-x}} \implies -\sum_{k=0}^{\infty}k e^{-k x}$$

$$= \frac{d}{dx}\frac{1}{1-e^{-x}}. $$


share|cite|improve this answer
@anorton: Thanks for the edit. – Mhenni Benghorbal Feb 16 '13 at 1:59

$$\int_0^\infty \lfloor x \rfloor e^{-x}dx = \sum_{n=1}^{\infty} \int^{\infty}_n e^{-x} dx= \sum_{n=1}^{\infty} e^{-n}=\frac{1}{e-1}.$$

share|cite|improve this answer
This is a great way to look at it! – Mark May 22 '13 at 1:41

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.